2003
DOI: 10.1002/pmic.200300462
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally induced changes of the proteome in the protozoan parasite Leishmania donovani

Abstract: In order to proceed through their life cycle, protozoan parasites of the genus Leishmania cycle between sandflies and mammals. This change of environment correlates with the differentiation from the promastigote stage (insect form) to the amastigote stage (intracellular mammalian form). The molecular basis underlying this major transformation is poorly understood so far; however, heat shock protein 90 (HSP90) appears to play a pivotal role. To further elucidate this process we identified proteins expressed pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
115
1
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 58 publications
12
115
1
9
Order By: Relevance
“…Only consistently overrepresented spots were further analyzed. The proteins in the gel plugs were destained, digested with trypsin (Promega), extracted, purified on a C18 reverse-phase matrix, and eluted in 8 ml 60% acetonitrile and 0.1% trifluor-acetic acid (24). A total of 2.5 ml of the eluted peptides were spotted onto a 378-well, 400-mm Anchor Plate (Bruker Daltonics, Bremen Germany).…”
Section: Two-dimensional Gel Electrophoresis and Maldi-tof Mass Spectmentioning
confidence: 99%
See 1 more Smart Citation
“…Only consistently overrepresented spots were further analyzed. The proteins in the gel plugs were destained, digested with trypsin (Promega), extracted, purified on a C18 reverse-phase matrix, and eluted in 8 ml 60% acetonitrile and 0.1% trifluor-acetic acid (24). A total of 2.5 ml of the eluted peptides were spotted onto a 378-well, 400-mm Anchor Plate (Bruker Daltonics, Bremen Germany).…”
Section: Two-dimensional Gel Electrophoresis and Maldi-tof Mass Spectmentioning
confidence: 99%
“…The sediment was resuspended in 50 ml PBS, and 150 ml rehydration buffer (8 M urea, 2 M thiourea, 4% CHAPS, and 2.4% aminosulfobetaine-14) was added. Two-dimensional protein electrophoresis was performed essentially as described previously (24).…”
Section: Two-dimensional Gel Electrophoresis and Maldi-tof Mass Spectmentioning
confidence: 99%
“…These axenic amastigotes resemble animal-derived amastigotes and have been widely used for investigating parasites activities without the complication of host cell material [20][21][22][23]. Time-course analysis of L. donovani differentiation showed that promastigotes expressed the amastigote-specific A2 protein family within an hour of exposure to the intralysosomal environment and at five hours they start to transform to amastigote-shaped cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the differences during transformation and between the different life-cycle stages on the molecular level several groups resolved the proteome of L. infantum, L. donovani and L. mexicana promastigotes and amastigotes [19][20][21] and promastigotes upon reception of the transformation signal 22 or metacylics 23 .…”
Section: Identification Of Life Cycle Stage Specific Proteinsmentioning
confidence: 99%